Two new crayfishes of the genus Cambarus (Decapoda: Cambaridae) from Northern Alabama and South Central Tennessee, U.S.A. - Jones, Danny R.; Eversole, Arnold G. (Zootaxa, 2015)
Multivariate and univariate statistical analyses of morphometric data and examination of morphological characters of the crayfish species Cambarus (Hiaticambarus) longirostris revealed the existence of two undescribed species from populations previously considered to be C. longirostris in tributaries of the Tennessee River in north Alabama and central south Tennessee. Cambarus (Hiaticambarus) andersoni and Cambarus (Hiaticambarus) diupalma differed from C. longirostris and from each other in aspects of chela morphometrics and in the presence or absence of qualitative characters. Cambarus andersoni has a corneous spine on the base of the ventral surface of the rostrum that is absent in the other two species; C. diupalma abdominal pleura are acute whereas they are subtruncate in C. andersoni and in C. longirostris. The known range of both of the new species is restricted to northern tributaries of the Tennessee River in south Tennessee and north Alabama. Cambarus diupalma is considered Endangered and C. andersoni is considered Vulnerable using American Fisheries Society conservation categorization.